Women's Livelihood Strategies and Sustainable Ecosystems in the Mahakam Estuary - Hastuti; Arum Sekar Kedhaton sekar; Nurul Khotimah; Nur Ariyanto (Indonesian Social Work Consortium (ISWC), 2026)
This study aims to identify accessible livelihood resources for women, analyze the factors contributing to the marginalization of women in accessing livelihood resources, and develop a model for women's involvement in sustainable ecosystem management. The research was conducted in the Mahakam River Estuary, East Kalimantan. The study employed a mixed-methods approach, incorporating both quantitative and qualitative methods. The sample was obtained using purposive random sampling, with a total of 60 women household members. Informants included forestry extension officers from Delta Mahakam, female leaders of micro, small, and medium enterprises organizations, and women from forest farmer groups in the Mahakam Estuary region. The findings indicate that women in the Mahakam Estuary have access to various natural resources. Women in the Mahakam Estuary adopt livelihood strategies through yard and pond intensification and extensification techniques. Engagement in social networks, training, and capital assistance enhances the economic capacity of women in the Mahakam Estuary. Women's roles in sustainable ecosystem management in the Mahakam Estuary include utilizing abiotic and biotic components to support livelihoods and the economy. Women are also involved in coastal ecosystem conservation efforts by planting various types of mangroves.